Análise energética do novo sistema de produção de maracujá amarelo na região de Marília-SP - Furlaneto, Fernanda de Paiva Badiz; Esperancini, Maura Seiko Tsutsui [UNESP]; Martins, Adriana Novais; Okamoto, Fumiko; Vidal, Anelisa de Aquino; Bueno, Osmar de Carvalho [UNESP] (Univ Federal Santa Maria, 2014)
The study aimed to evaluate energy indicators of a new production system of yellow passion fruit in Marília-SP. Analyzed the inputs of the biological energy, fossil and industrial and output energy in the form of fruits produced per unit area as well as five energy indicators. The input energy amounted 155,810.13MJ ha-1. Chemical fertilizers and pesticides accounted for 71% and 24% of indirect energy industry, respectively. The activity generated per cycle / ha, 587.700.00MJ, and cultural productivity 0.19MJ kg-1. The efficiency culture was 3.77. The cultural energy net totaled 431,889.87MJ ha-1. The energy efficiency (4.17) and energy balance (550,312.91MJ ha-1) was favorable. It was concluded that the direct energy consumption from fossil fuels, even though significant, yet permits the production of the fruit of an environmentally sustainable manner. Chemical fertilizers and pesticides were the most representative of indirect energy industry due to the intensification of fertilization as a means of disease prevention.
Energy analysis of new production system of yellow passion in region of Marília-SP, Brazil
Keywords: Passiflora edulis f. flavicarpa; energy efficiency; energy balance